The disinformation age : politics, technology, and disruptive communication in the United States - Bennett, W. Lance; Livingston, Steven (Writer on public affairs) (New York, NY : Cambridge University Press, 2021)
"The authors gathered here are distinguished representatives of the interdisciplinary perspectives of history, political science, sociology, law, and communication - fields that are all helpful to understanding the origins and importance of the problem. While some observers approach disinformation as something that has just emerged seemingly from nowhere, the chapters in this book trace various origins such as: the history of business deception to promote corporate interests over the public interest, government lying to promote dubious policies, and the rise of political influence networks that limit government capacities to represent the public interest. These historical factors have contributed to the erosion of trust in public institutions, and related declines in confidence in the news media that have traditionally connected public authorities and citizens. As authoritative information becomes increasingly challenged, new digital platforms and social media networks supply the demand for alternative political truths that are actively consumed by disaffected citizens. The growing volume of disinformation fuels political movements and parties largely on the radical right, resulting in attacks on the press, the spread of hate and propaganda, efforts to exclude various minority groups, and the rise of ethnic nationalism in many nations. The book traces the origins of this decline of institutional authority, the state of current disinformation systems, the historical origins of systemic disinformation, the importance of independent public media, and possible regulatory and political remedies for these problems"--
Keywords: Communication in politics -- United States; Disinformation -- United States